We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
138
1
avatar

http://prntscr.com/mvjxsf

 Mar 9, 2019
 #1
avatar+105327 
0

Avg rate of change =

 

[ f(-2) - f(-5) ]

___________   =

   -2 -  (-5)

 

[ (-2)^2 - 4 ] - [ (-5)^2 - 4 ]

_____________________    =

              3

 

[ 4    -   25 ] 

__________    =

       3

 

 

[ -21 ]

_____   =   

    3

 

 

-7

 

 

cool   cool   cool

 Mar 9, 2019
edited by CPhill  Mar 9, 2019

26 Online Users

avatar
avatar